53BP1: function and mechanisms of focal recruitment. (22nd July 2009) - FitzGerald, Jennifer E.; Grenon, Muriel; Lowndes, Noel F.
Abstract : 53BP1 (p53-binding protein 1) is classified as a mediator/adaptor of the DNA-damage response, and is recruited to nuclear structures termed foci following genotoxic insult. In the present paper, we review the functions of 53BP1 in DNA-damage checkpoint activation and DNA repair, and the mechanisms of its recruitment and activation following DNA damage. We focus in particular on the role of covalent histone modifications in this process.